2005
DOI: 10.1177/1471301205055034
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of reports of caregiver burden between foster family care providers and staff caregivers in other settings

Abstract: There has been increasing concern about the impact of dementia symptoms on the lives and on the care being provided for persons with intellectual disability (ID) in out-of-home settings. One such setting that has received little attention is foster family care homes. These settings in the USA replicate family living and while some supports and resources are provided, they are not designed to meet intensive care needs. As a preliminary step in understanding family experiences and to expand the range of interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…For example, moderate congruence (Werner et al, 1988; Cohen-Mansfield, 2002) has been reported for pain assessment. More recently, McCallion et al (2005) found no significant differences between traditional staff and foster family caregivers in reports of subjective or objective caregiver burden with respect to a sample of adults with intellectual disabilities and/or Alzheimer’s disease living in a foster family setting. Another study comparing staff and family ratings of the resident’s unmet need in a sample of adults diagnosed with dementia and living in an assisted living facility, found no differences in the perceptions of these informants (Milke et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…For example, moderate congruence (Werner et al, 1988; Cohen-Mansfield, 2002) has been reported for pain assessment. More recently, McCallion et al (2005) found no significant differences between traditional staff and foster family caregivers in reports of subjective or objective caregiver burden with respect to a sample of adults with intellectual disabilities and/or Alzheimer’s disease living in a foster family setting. Another study comparing staff and family ratings of the resident’s unmet need in a sample of adults diagnosed with dementia and living in an assisted living facility, found no differences in the perceptions of these informants (Milke et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Most studies reported in the literature relate to the experiences and issues of staff in ID services providing care to persons with ID and dementia. Comparing subjective and objective measures of burden, few differences have been found between staff carers in ID service settings and foster family situations (McCallion, Nickle, & McCarron, 2005). Little work exists reporting specifically on caregiving in the family context (an exception is Janicki, Zendell, & DeHaven, in press).…”
Section: Carer Issuesmentioning
confidence: 99%
“…Research-Postal questionnaire n = 35 of 45 members of DS Scotland responded (family and paid staff carers) Finnamore and Lord (2007) To determine use of Dementia Care Mapping in service planning for adults with ID and dementia Research-Intervention n = 8 adults with ID diagnosed with dementia living in hospital or community home in England Janicki and Wilkinson (2007) To investigate national practices related to dementia and ID Research-International survey n = 35 of 77 National AD organizations affiliated with ADI Kalsy, Heath, Adams, and Oliver (2007) To investigate effects of training, behavior, and biological context on staff attributions of challenging behavior Research-Intervention evaluation. Pre-and post-training questionnaires n = 97 community day center staff in UK who attended training on aging, dementia and ID Kerr, Cunningham, and Wilkinson (2006) To explore the identification and management of pain amongst people with ID and dementia Research-Interviews and observations n = 49 support staff, 31 professionals, and n = 12 adults with ID and dementia interviewed or observed Janicki, Dalton, McCallion, Baxley, and Zendell (2005) To examine physical features, adaptation to behavior change, and demands on staff in small group homes for persons with ID and dementia Research-Modified ethnographic study and questionnaire n = 12 group homes in Australia, Canada, Japan, Sweden, and the U.S. n = 10 group homes from UK and the U.S. Site completed questionnaires on the home and staff, and selected residents McCallion, McCarron, and Force (2005) To develop measure of subjective burden for staff carers Research-CDS-ID instrument development n = 203 staff of services for adults with ID and dementia in Ireland and the U.S. McCallion, Nickle, and McCarron (2005) To compare caregiver burden between foster family and staff carers Research-questionnaires n = 14 people with ID/AD from foster families matched with n = 14 people from other out-of-home arrangements in the U.S. Carers completed DMR, CAS-ID and CDS-ID McCarron, Gill, McCallion, and Begley (2005) To investigate the amount of time staff carers spend on day-to-day care for persons with DS, with and without dementia…”
Section: Service Provision and Organizational Contexts Of Caregivingmentioning
confidence: 99%